2014
DOI: 10.1007/s00270-014-0928-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Following a Negative CT Angiogram for Gastrointestinal Hemorrhage

Abstract: Objective This study was designed to evaluate the role of a negative computed tomography angiogram (CTA) in patients who present with gastrointestinal (GI) hemorrhage. Methods A review of all patients who had CTAs for GI hemorrhage over an 8-year period from January 2005 to December 2012 was performed. Data for patient demographics, location of hemorrhage, hemodynamic stability, and details of angiograms and/or the embolization procedure were obtained from the CRIS/PACS database, interventional radiology datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…found that 77% of patients with negative studies did not need further intervention. In 68% of cases the exam did not show features of active bleeding, which is consistent with the present findings [7]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…found that 77% of patients with negative studies did not need further intervention. In 68% of cases the exam did not show features of active bleeding, which is consistent with the present findings [7]. …”
Section: Discussionsupporting
confidence: 92%
“…reporting about 90% of patients with LGIB and positive CTA needing intervention for bleeding control. However, surgery was performed in 24% of cases whereas embolization was successful in 64% of patients [7]. In a study from Nagata & al., early colonoscopy following CTA resulted in a higher detection rate of colonic vascular lesions than colonoscopy alone [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTMAs can be falsely negative when bleeding is <0.5 mL/min or in the presence of intermittent bleeding, and should be used in those with brisk ongoing bleeding that is not amenable or not effectively treated by colonoscopy . In a study evaluating outcomes following negative CTMA, 22% of 115 cases developed subsequent acute bleeding requiring further radiological or surgical intervention within the same admission . The overall yield of CTMA is 50–70%, with 65–85% of these resulting in haemostasis if mesenteric angiograms and angioembolization were successful .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst most resolve spontaneously, 20–30% continue to bleed torrentially, necessitating invasive interventions such as angioembolization, endoscopic haemostatic techniques or emergency surgery . Angioembolization following a positive computed tomography mesenteric angiogram (CTMA) is useful, but a negative CTMA in the setting of intermittent severe bleeding limits its role . As the identification of specific culprit diverticulum during colonoscopy is difficult, direct therapeutic options such as clipping, adrenaline injection and band ligation are limited.…”
Section: Introductionmentioning
confidence: 99%